The Poetics and Politics of Code-Switching in Chimamanda Ngozi Adichie’s Americanah - Bhusal, Damodar (Butwal Campus Journal, 2025)
Chimamanda Ngozi Adichie's Americanah (2013) represents a masterful exploration of postcolonial identity through the sophisticated deployment of code-switching as both aesthetic technique and political commentary. This novel transcends conventional narrative boundaries by employing strategic shifts between Nigerian English, Standard American English, and African American Vernacular English (AAVE) to illuminate the complex negotiations of identity, power, and belonging experienced by transnational subjects. Through an interdisciplinary approach combining sociolinguistic analysis with postcolonial theory, this study reveals how Adichie's linguistic choices function simultaneously as poetic devices that enrich narrative texture and as political instruments that challenge hegemonic language ideologies. The analysis demonstrates that code-switching in Americanah operates at multiple levels: as a mechanism for character development, a tool for cultural critique, and a means of asserting linguistic sovereignty in postcolonial and diasporic contexts. By examining specific textual instances alongside theoretical frameworks including the Social Meaning Hypothesis, Accommodation Theory, and concepts of linguistic hybridity, this study argues that Adichie's strategic code-switching constitutes a form of literary activism that both celebrates linguistic diversity and exposes the power structures embedded in language hierarchies.